POLISH AND ENGLISH LOCATIVE EXPRESSIONS: AN OVERVIEW - Łozińska, Joanna (Acta Neophilologica, 2013)
The aim of the article is to outline the main differences and similarities in the ways spatial relations are expressed by means of prepositions in English and in Polish. The discussion starts with classifying the two languages within the same system of space conceptualization. Then, a description of prepositions is presented. The article concludes with the comparison of the dynamic aspects of the Polish prepositions do ‘to’, ‘into’, w ‘in’, ‘into’ and na ‘on’, ‘onto’ and their English equivalents to, in and on. Next, the main emphasis will be put on the way space is structured in Polish by means of other spatial terms, which include prefixes to the verbs, direction nouns and noun cases.